La gestión del talento humano y el desempeño laboral de la empresa pública municipal mercado de productores san pedro de Riobamba EP-EMMPA. - Viviana Alexandra, Asqui Leiva (2020)
ABSTRACT: This research work was developed to demonstrate how human talent management influences the work performance of the Public Municipal Company Producers' Market "San Pedro de Riobamba", knowing that there are shortcomings in the area of human talent which has caused unsatisfactory work performance. This research details the problems related to human talent in EP-EMMPA that affect the company’s good development in terms of employee performance and job satisfaction. In the section on the state of the art and theoretical framework is the information regarding the research variables used to support the research. The methodology includes the type of research, which is descriptive, explanatory, field, and bibliographic; it is non-experimental research, and the information was collected through a survey aimed at EP_EMMPA employees and workers. Tables and graphs, represent the result of information processing. The factors that influence job performance can be verified. The statistical analysis of the hypothesis verification was done through the Chi-square test, resulting in the management of human talent influences work performance of the EP-EMMPA. The results helped to draft the conclusions and recommendations. Finally, objective strategies were designed to improve teamwork and, therefore, the work environment, significantly affected the EP-EMMPA.